Effects of Metformin in Experimental Stroke - Li, Jun (2010)
BACKGROUND AND PURPOSE: AMP-activated protein kinase (AMPK) is an important sensor of energy balance. Stroke-induced AMPK activation is deleterious as both pharmacological inhibition and genetic deletion of AMPK are neuroprotective. Metformin is a known AMPK activator, but reduces stroke incidence in clinical populations. We investigated the effect of acute and chronic Metformin treatment on infarct volume and AMPK activation in experimental stroke. METHODS: Male mice were subjected to middle cerebral artery occlusion (MCAO) after acute (3 days) or chronic (3 weeks) administration of Metformin. Infarct volumes, AMPK activation, lactate accumulation, and behavioral outcomes were assessed. The role of neuronal Nitric Oxide Synthase (nNOS) and AMPK were examined using mice with targeted deletion of AMPK or nNOS. RESULTS: Acute Metformin exacerbated stroke damage, enhanced AMPK activation, and led to metabolic dysfunction. This effect was lost in AMPK and nNOS knockout mice. In contrast, chronic Metformin given pre-stroke was neuroprotective, improved stroke-induced lactate generation, and ameliorated stroke-induced activation of AMPK. Similarly the neuroprotective effect of chronic pre-stroke Metformin was lost in nNOS knockout mice. CONCLUSIONS: AMPK is an important potential target for stroke treatment and prevention. These studies show that the timing, duration and amount of AMPK activation are key factors in determining the ultimate downstream effects of AMPK on the ischemic brain.